2021
DOI: 10.1002/tcr.202100145
|View full text |Cite
|
Sign up to set email alerts
|

1,2‐Aminofunctionalization Reactions of Pyridino‐Alkynes via Carbophilic Activation

Abstract: Transition metal-catalyzed 1,2-difunctionalization reactions of alkynes have emerged as a powerful tool to forge carbon-carbon and carbon-heteroatom bonds for the rapid synthesis of polyfunctionalized molecular scaffolds. In this regard, our group has persistently been developing transition metal-mediated 1,2-aminofunctionalization reactions of alkynes through a rationally designed pyridino-alkyne core by utilizing the carbophilic activation strategy. In this account, we present an array of such 1,2-aminofunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…One of the authors of the manuscript, have earlier reported a series of reactions on the metal‐catalysed cyclization reactions of pyridino‐alkynes [14] to access new fluorophores [15] . Inspired by these results, we recently developed a library of AIEgens through an endo ‐selective silver‐mediated cyclization of pyridino‐alkynes Py‐Alk to access benzo[a]quinolizinium‐base dionic AIEgens BQ (Scheme 3).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…One of the authors of the manuscript, have earlier reported a series of reactions on the metal‐catalysed cyclization reactions of pyridino‐alkynes [14] to access new fluorophores [15] . Inspired by these results, we recently developed a library of AIEgens through an endo ‐selective silver‐mediated cyclization of pyridino‐alkynes Py‐Alk to access benzo[a]quinolizinium‐base dionic AIEgens BQ (Scheme 3).…”
Section: Figurementioning
confidence: 99%
“…One of the authors of the manuscript, have earlier reported a series of reactions on the metal-catalysed cyclization reactions of pyridino-alkynes [14] to access new fluorophores. [15] Inspired by Scheme 1. AIEgens through anion-π + interaction: An initial report.…”
mentioning
confidence: 99%
“…There have been reviews that focus on optimization studies and reactivities in gold catalysis; , however, a thematic review on the development of homogeneous sustainable gold catalysis at a ppm level has remained highly sporadic in the literature. , In light of our long-standing interest in the development of homogeneous gold catalysis, herein, we would like to present a comprehensive perspective summarizing all the reports that employ catalyst loadings ≤ 0.1 mol %. A special emphasis on the roles of electronic and steric effects of ligands to achieve high turnover numbers (TONs) and turnover frequencies (TOFs) are given for a better understanding for the readers.…”
Section: Introductionmentioning
confidence: 99%
“…However, such reports remain highly sporadic in literature. [24][25][26] Inspired by our ongoing interest in catalytic carbophilic activation and especially developing metal-catalyzed cyclization reactions of pyridino-alkynes to access fluorophores; [30][31][32][33][34] herein, we disclose a method to access a library of AIEgens based on the interplay of anion-π + , π + -π + and other non-covalent interactions. A significant impact of substituents, their position, and the nature of counterions, was found to be important in modulating their photophysical properties.…”
Section: Introductionmentioning
confidence: 99%